Planococcus Species – An Imminent Resource to Explore Biosurfactant and Bioactive Metabolites for Industrial Applications - Waghmode, Samadhan; Suryavanshi, Mangesh; Sharma, Deepansh; Satpute, Surekha K. (Frontiers in Bioengineering and Biotechnology, 2020)
The marine environment represents a well-off and diverse group of microbes, which offers an enormous natural bioactive compounds of commercial importance. These natural products have expanded rigorous awareness due to their widespread stability and functionality under harsh environmental conditions. The genus Planococcus is a halophilic bacterium known for the production of diverse secondary metabolites such as 2-acetamido-2-deoxy-α-d-glucopyranosyl)-(1→2)-β-d-fructofuranose exhibiting stabilizing effect and methyl glucosyl-3,4-dehydro-apo-8-lycopenoate displaying antioxidant activity. The genus Planococcus is reported generally for hydrocarbon degradation in comparison to biosurfactant/bioemulsifier secretion. Although Planococcus was proposed in 1894, it seized long stretch (till 1970) to get accommodated under the genus Planococcus authentically. Large scale biosurfactant production from Planococcus was reported in 2014 with partial characterization. For the first in 2019, we documented genomic and functional analysis of Planococcus sp. along with the physico-chemical properties of its biosurfactant. In 2020, again we screened biosurfactant for pharmacological applications. The present review discusses the comprehensive genomic insights and physical properties of Planococcus derived biosurfactant. Moreover, we also highlight the prospects and challenges in biosurfactant production from Planococcus sp. Among ~102 reports on biosurfactant produced by marine bacteria, 43 were of glycolipid and 59 were non-glycolipid type. Under other biosurfactant type they were identified as lipopeptide (20) like surfactin (5); glycolipoprotein/lipoprotein (12); other non-glycolipid (22). Planococcus sp. generally produces glycolipid type biosurfactant (4) and exopolysaccharides (2). The single report documented in the literature are on biosurfactant production (glycolipid +non glycolipid) by diverse marine microbes (39) suggesting their novelty and diversity for biosurfactant secretion.